Diabetes medication use and blood lactate level among participants with type 2 diabetes: the atherosclerosis risk in communities carotid MRI study. - Morgana L Mongraw-Chaffin; Kunihiro Matsushita; Frederick L Brancati; Brad C Astor; Josef Coresh; Stephen O Crawford; Maria Inês Schmidt; Ron C Hoogeveen; Christie M Ballantyne; Jeffery Hunter Young (PLoS ONE, 2012)
The objective of this study is to compare lactate levels between users and non-users of diabetes medications under the hypothesis that the level of lactate is a marker of oxidative capacity.The cross-sectional data of 493 participants aged 61-84 with type 2 diabetes who participated in the Atherosclerosis Risk in Communities Carotid MRI study were analyzed using survey weighted linear regression.Median plasma lactate level was 8.58 (95% CI: 8.23, 8.87) mg/dl. Comparing users of diabetic medications with non-users, thiazolidinedione use was significantly associated with lower lactate level (7.57 (6.95-8.25) mg/dL vs. 8.78 (8.43-9.14) mg/dL), metformin use with a slightly higher lactate level (9.02 (8.51-9.58) mg/dL vs. 8.36 (7.96-8.77) mg/dL), and sulfonylurea and insulin use were not associated with lactate level. After adjustment for demographic and lifestyle factors, the plasma lactate level for thiazolidinedione users was 15.78% lower than that for non-users (p<0.001). Considering use of each medication separately and in combination did not change the results.In conclusion, thiazolidinedione use was associated with lower plasma lactate level compared to non-use and metformin use was only marginally associated with a slightly higher lactate level. These results are consistent with the previously demonstrated effects of diabetes medications on oxidative metabolism. Further investigation of the role that diabetes medications play in improvement of oxidative metabolism is warranted.